PENGGUNAAN MEDIA KARTU SEBAGAI STRATEGI DALAM PEMBELAJARAN MEMBACA PERMULAAN : STUDI KASUS DI MADRASAH IBTIDAIYAH NEGERI RUKOH, BANDA ACEH - . Khairunnisak (Jurnal Pencerahan, 2015)
The utilisation of flash cards is one of the teaching methods in early literacy learning of the subject of Bahasa Indonesia (Indonesian Language). These are simply cards that display the written words. Flash cards can be bright and colourful and make a real impact on visual learners. Among many methods, it was considered one of the best fits for children at reading age. This article aims to determine the extent to which the use of flash card as a medium of learning could improve the reading skills of students of class I at the Madrasah Ibtidaiyah Negeri-MIN (National Islamic Elementary School) Rukoh, Banda Aceh for the academic year of 2012/2013. This study is a Classroom Action Research (CAR), which is the research conducted in a classroom using the specific learning media, which in this regard is the flash cards. Data for this study was gathered through experiments, observation during the learning process, and interview with several selected teachers and students. Data were then analysed using the descriptive-comparative technique, in which each test results of the students’ reading abilities were compared to each other. The study found that the teaching process using flash cards as a medium of learning was able to improve early reading skills of students of MIN Rukoh, Banda Aceh